2007
DOI: 10.1111/j.1365-2559.2007.02655.x
|View full text |Cite
|
Sign up to set email alerts
|

S100A1: a powerful marker to differentiate chromophobe renal cell carcinoma from renal oncocytoma

Abstract: S100A1 may be a potentially powerful marker to differentiate the chromophobe RCC from renal oncocytoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(57 citation statements)
references
References 22 publications
4
53
0
Order By: Relevance
“…A lot has been published in relation to the diagnostic differential between the ChRCC and the RO, with multiple works that demonstrate differences between expression markers in both tumors, however most of them correspond to markers with little diffusion or infrequent use in the anatomic-pathological routine. Among them are S100-A1, Claudins 7 and 8, Endogenous Abidin binding, PAX2, RON, LMP2, Cytochrome C Oxidase and others [10][11][12][13][14][15]. However, data suggests that a set of markers is much better that a single marker, besides a rigorous revision and meticulous analysis of the morphology even architectural and cytological parameters [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot has been published in relation to the diagnostic differential between the ChRCC and the RO, with multiple works that demonstrate differences between expression markers in both tumors, however most of them correspond to markers with little diffusion or infrequent use in the anatomic-pathological routine. Among them are S100-A1, Claudins 7 and 8, Endogenous Abidin binding, PAX2, RON, LMP2, Cytochrome C Oxidase and others [10][11][12][13][14][15]. However, data suggests that a set of markers is much better that a single marker, besides a rigorous revision and meticulous analysis of the morphology even architectural and cytological parameters [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The CK7 is an intermediate filament classically described in the ChRCC, with a diffuse expression in cytoplasm and membrane [4,8,11,16,17] with expression levels that fluctuate among the 63% and 100% of the cases. This pattern is found in almost all cases of our series, but sometimes is observed only in a part of the neoplasm, being negative in other areas.…”
Section: Discussionmentioning
confidence: 99%
“…S100A1 is a member of the S100 family of calcium binding molecules, most of which are clustered on chromosome 1q21, and expressed in RCC (Teratani et al 2002). Importantly, these proteins are involved in cell cycle progression and cell differentiation (Li et al 2007) and therefore implicated in tumorigenesis, a basis for investigation of S100A1 in renal tumour subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Individual and pooled OR results are shown in a Forest plot in Figure 3.3. (Carvalho et al 2011;Kim et al 2009;Kuroda et al 2011;Li et al 2007) The pooled OR (chRCC compared to RO) was 0.01 (95% CI 0-0.03), with I 2 = 0%. Therefore, the OR of RO compared to chRCC for S100A1 staining is 100 and I 2 study heterogeneity revealed similar consistency between the effects of the 4 studies.…”
Section: S100a1mentioning
confidence: 99%
See 1 more Smart Citation